The Professional Experience Changes of Teachers in Poland - Beata Cieśleńska (Lesya Ukrainka Volyn National University, 2020)
Introduction. Improvement of teachers is entered in the educational system of each country. It largely depends on the political and socio-cultural expectations of the state. Improvement is aimed at raising the qualifications and competences of teachers, whose knowledge and skills directly translate into the educational success of the pupils. The need to raise awareness of the value of work was a key guarantee for teachers in Poland to keep up with the changing educational and social realities. The Research Aim is to analyse the teacher`s system development in Poland during the post-war period and the beginning of the XXI century. The Research Methods. Analysis of historical and pedagogical literature on the theory and practice of teacher training at schools in Poland. The Research Results. In Poland the issue of teacher training has always received considerable attention. As in other countries, a teacher training system was created, which would be the subject of in-depth analysis and controversy. Over the last decades, the legal framework for teacher training in Poland changed in line with the political situation in education. The importance of institutions that trained teachers and passed state accreditation has increased. The number of non-governmental institutions, involved in teacher retraining, has also increased. The number of non-governmental institutions has also been growing systematically. In-service, training is a key element in the professional development of a teacher. In the teacher improvement development during post-war Poland, at least several stages can be distinguished: the initial period characterized by the diversity and structural incoherence of teacher training; the period of reaching the rational concept of teachers' professional development; a period of full uniformity in the improvement of teachers; the period of building a system of continuing teacher education at the post-graduate level; period as the activity of the Teacher Training Institute and its branch offices stabilizes; development of post-graduate studies and qualification courses for teachers. After 2000s teacher training takes place at three categories: as self-education, intra- school teacher training [WDN] and institutional improvement outside of school. Contemporary professional development of teachers in Poland is also multithreaded, both institutional and non-institutional. Although during the last decades the self-education activity of teachers has increased, institutional forms that improve the skills and competences are still dominant. Instrumental improvement, which is instrumentally treated, unfortunately, but a limited extent, plays the role of a stimulator in the professional teacher development. Therefore, it is necessary to undertake various activities aimed at maintaining the motivation for the development and professional development of teachers. Conclusion. The instrumentally defined process of professional retraining, unfortunately, does not fully, plays the role of stimulator of teacher deve- lopment. Therefore, the process of gradual changes in the teachers` pedagogical activities require not only external control, but also the activity of the teachers, particularly, their acceptance of those values and aspirations as serve-development